Persepsi Generasi Z Pada Film Nanti Kita Cerita Tentang Hari Ini - Damanik, Fransiscus Bonahara; Salmaniah Siregar, Nina Siti; Barus, Rehia K Isabela (Universitas Medan Area, 2024)
This study aims to understand the perception and description of Generation Z's emotions and to find out the denotative and connotative meanings interpreted by Generation Z in watching the film NKCTHI. Using qualitative methods by collecting data through interviews, documentation, observation, porpusive sampling technique and using an interactive model from Miles Huberman to analyze the data. The literature review is a perception model that is correlated with emotion and Roland Barthes' semiotic theory. The results of this study present fluctuating emotions and emotions that accumulate to the peak of sadness and emotion when watching. This atmosphere comes from the closeness, the emotional characteristics of the film, and the conflict that is designed to be real and natural like personal life and the importance of family life for Generation Z. Meanwhile, the denotative and connotative meanings that are connected with signs have emotional tones and have special meanings or emotive meanings; connotative meaning in channeling meaningful lessons.